Effects of expansive filler and headed rebar on the shortening of development length of mortar-filled joints. (August 2021) - Murakami, Rikiya; Onoue, Kozo; Morimoto, Kento; Hashimoto, Ryota
Abstract: In this paper, the shortening of the development length of mortar-filled joints that connect precast concrete members is studied focusing on the use of expansion fillers and headed rebars. Rebars with a diameter of 13 mm are used. First, specimens are prepared with different dosages of lime-based expansive additive containing calcium oxide as the main component in commercial high-strength-non-shrink mortar or low-viscosity grout. It is found that the load-bearing performance of the mortar-filled joint is improved when the expansive additive is added to the high-strength-non-shrink mortar. However, in all cases, pullout failure occurs and rebar failure cannot be achieved. Second, a cement-based-highly-expansive filler mainly composed of calcium oxide and silicate with a swelling pressure of 40 N/mm 2 or more at 3 days is employed. As a result, it is found that the rebar failure can be achieved for a development length of 4  d (52 mm). To further shorten the development length, headed rebar is then used as an inserted rebar. The test results show that rebar failure can be achieved when using a comparatively short development length of 3.5  d (45.5 mm). It is concluded that the use of a cement-based-highly-expansive filler and a headed rebar is effective in shortening the development length of mortar-filled joints. Highlights: A new type of mortar-filled joint with short development length is proposed. Combined use of headed rebar and cement-based-highly-expansive filler is the key. Using those technologies, relatively short development length of 3.5 d is achieved.